Spectral characteristics and thermal evolution of long-period gratings in photonic crystal fibers fabricated with a near-IR radiation femtosecond laser using point-by-point inscription - Kalli, Kyriacos; Allsop, Thomas P.; Zhou, Kaiming; Smith, Graham N.; Komodromos, Michael; Petrović, Jovana S.; Webb, David; Bennion, Ian (My University, 2011)
The spectral properties of long-period gratings (LPGs) fabricated in photonic crystal fibers using femtosecond laser pulses by the point-by-point technique, without oil-immersion of the fiber, are investigated in detail. Postfabrication spectral monitoring at room temperature showed significant long-term instability of the gratings and stable spectra only after 600 h. The stabilized spectral properties of the gratings improved with increasing annealing temperature. The observed changes in resonant wavelength, optical strength, and grating birefringence were correlated to the laser inscription energy and were further used to study the mechanism of femtosecond inscription. Furthermore, the femtosecond-laser inscribed LPGs were compared to electric-arc fabricated LPGs. Comparison of experimental results with theoretical models of LPGs and laser propagation during inscription indicate that the major processes responsible for the index change are permanent compaction and thermally induced strain, the latter can be significantly changed through annealing.
Keywords: Crystal whiskers; Photonic crystals; Photonic crystals; Fibers